Historia, olvido y recuerdo en Hegel y Nietzsche - Gama, Luis Eduardo (2007)
“History, forgetfulness and remembrance in Hegel and Nietzsche”. Albeit the evident distance between Hegel´s and Nietzsche´s philosophical projects, there is a shared terrain from which both authors respond to the excesses of modern illustration, which reacted against history and tradition, in the name of a subjective conscious understood as the unconditioned nucleus of reality. This paper wants to contribute to show how close to each other are this so called antagonists, showing that in their doctrines there is an intuition about the fundamental temporality that lies in human existence and experience. From this common point of view, articulated in both cases with the notions of “remembrance” and “forgetfulness”, it is the purpose to generate a living dialogue, however full of tensions, between Hegel and Nietzsche, as critics of Modernity.